Investigation of Various Coating Resins for Optimal Anticorrosion and Mechanical Properties of Mild Steel Surface in NaCl Solution - Sandeep V. Gujjar; Nandini Nadar; Kanaram Choudhary; Anand M. Hunashyal; Kiran Shahapurkar; M. A. Mujtaba; Mohammed Asadullah; Manzoore Elahi M. Soudagar; T. M. Yunus Khan; Khadiga Ahmed Ismail; Ashraf Elfasakhany (Advances in Materials Science and Engineering)
The primary objective of the research was to investigate the ideal resin coating on the mild steel surface among various resin coatings which are in use. These resin coatings are used as an anti-corrosive material for mild steel surfaces with enhanced mechanical properties. The resins (epoxy, polyurethane, polyester, and phenolic) on mild steel surface were applied by the pneumatic spray coating method. In addition, immersion test and salt spray test methods were followed using sodium chloride (NaCl) solution. Furthermore, the rate of corrosion and mechanical properties of mild steel coated with different resins was evaluated by conducting various experiments (immersion test, salt spray test, tensile strength test, and scratch hardness test) and was compared with a bare mild steel surface. The results of the current research showed that the mild steel surface coated with epoxy resin was found to be the most effective corrosion resistance material with better mechanical properties compared to other tested mild steel resin-coated surfaces.